2020
DOI: 10.1016/j.strueco.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The effects of monetary policy on income and wealth inequality in the U.S. Exploring different channels

Abstract: We assess the effects of monetary policy shocks on income and wealth inequality through direct inequality measures and by analyzing several transmission channels explored in recent literature. Furthermore, we analyze two additional channels: the Housing and the Fiscal channels. The methodology adopted is a Bayesian proxy SVAR using a high-frequency identification based on the external instruments approach. Our own policy shocks are constructed for this purpose. The results show that an expansionary monetary po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…But this may benefit the wealthy more than the poor, as the wealthy tend to have more assets that will appreciate. Our results align with the findings observed in developed countries and other regions, such as Adam and Zhu (2016); Albert and Gómez-Fernández (2022) and Albert et al (2020).…”
Section: Impulse Response Function Of Pvar (supporting
confidence: 92%
See 2 more Smart Citations
“…But this may benefit the wealthy more than the poor, as the wealthy tend to have more assets that will appreciate. Our results align with the findings observed in developed countries and other regions, such as Adam and Zhu (2016); Albert and Gómez-Fernández (2022) and Albert et al (2020).…”
Section: Impulse Response Function Of Pvar (supporting
confidence: 92%
“…The nexus between monetary policy and wealth inequality is examined by following the empirical model by Coibion et al (2017) and Park (2021), who state that wealth disparity occurs because the expansionary monetary policy benefits the rich and the poor unevenly. Rich households with greater financial asset holding tend to benefit more from monetary shocks than poor households (Albert et al, 2020;Romer & Romer, 1998). The methodology of this study follows five steps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there is no dichotomy, as the economic system is one and one only: Monetary variables affect (and are affected by) real variables over any time horizon (short, medium, and long run). In particular, monetary policy affects income and wealth distribution along different transmission channels, namely, the interest rate channel, the balance-sheet channel, and the asset price channel (see Carré, 2015;Febrero and Uxó, 2015;Albert, Peñalver, and Perez-Bernabeu, 2020).…”
Section: The Distributive Impact Of Central Banks' Interventionsmentioning
confidence: 99%
“…There have been many studies used to find a unified answer to the above-mentioned problems in recent times. In countries with developed economies, studies have shown mixed results when evaluating how monetary policy affects income inequality and wealth redistribution between rich and poor, such as Alves and Silva (2021), Hohberger et al (2020), Ampudia et al (2018), Guerello (2018) and Lenza and Slacalek (2018) with the European economy; Albert and G omez-Fern andez (2018), Albert et al (2020), Doepke et al (2019) and Davtyan (2017) with the US economy; Mumtaz and Theophilopoulou (2020) with the UK economy; Israel and Latsos (2020) and Lee (2020) with the Japanese economy; Kuncl and Ueberfeldt (2021) with the Canadian economy; Zhang et al (2021) with the Chinese economy. Which Guerello (2018), Hohberger et al (2020) and Israel and Latsos (2020) study both conventional and unconventional monetary policy; Lenza and Slacalek (2018) and Lee (2020) assess the impact of quantitative easing on income distribution.…”
Section: Introductionmentioning
confidence: 99%